GOVERNMENT INTERNAL OVERSIGHT IN ENHANCING THE PERFORMANCE OF CIVIL SERVANTS - Kornelia Luaq; Kridawati Sadhana; Chandra Dinata (International Journal of Business, Law and Political Science, 2026)
Objective: Government internal supervision plays a strategic role in ensuring compliance, accountability, and improved performance among civil servants. This study aims to analyze the implementation of the government internal supervision policy based on Minister of Home Affairs Regulation Number 107 of 2017 at the Regional Inspectorate of West Kutai Regency and to identify the role and constraints of internal supervision in improving civil servant performance. Method: This study employed a descriptive qualitative approach. Data were collected through interviews with the Regional Inspector, auditors or Government Internal Supervisory Apparatus personnel, representatives of the Human Resources Development and Personnel Agency, and civil servants, supported by observation and documentation. Data were analyzed using the Miles, Huberman, and Saldaña model, comprising data condensation, data display, and conclusion drawing and verification. Results: The findings indicate that the internal supervision policy has generally been implemented through policy communication, resource support, implementers’ commitment, division of responsibilities, standard operating procedures, and the Annual Supervision Work Program. Novelty: Based on George R. Terry’s supervision indicators, the process includes establishing standards, measuring work performance, comparing actual performance with established standards, and taking corrective action. Internal supervision contributes to improving discipline, compliance, professionalism, administrative quality, and personnel accountability. However, its implementation remains suboptimal due to limited numbers and competencies of supervisory personnel, budgetary and infrastructure constraints, extensive supervisory coverage, weak evaluation documentation, inconsistent discipline, and limited commitment among some audited entities to follow up on recommendations. Therefore, internal supervision has positively contributed to civil servant performance but requires stronger supervisory capacity, monitoring systems, and consistent follow-up.